2002
DOI: 10.1007/s10350-004-6465-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined Perineal and Endorectal Repair of Rectocele by Circular Stapler

Abstract: Combined perineal and endorectal stapler repair of rectocele may be a useful new surgical tool for correcting distention rectocele associated with mucosal prolapse or hemorrhoids and perineal descent in selected patients. A longer follow-up on a larger number of patients is needed to confirm these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 13 publications
0
33
0
2
Order By: Relevance
“…The use of these physiologic investigations would be certainly advisable for comprehensive assessment of anorectal functional disorders. It is generally accepted that surgery for rectocele does not affect anal sphincter function as measured by manometry [1,2,3, 11, 12], though van Dam et al [26] reported a risk of impaired fecal continence after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of these physiologic investigations would be certainly advisable for comprehensive assessment of anorectal functional disorders. It is generally accepted that surgery for rectocele does not affect anal sphincter function as measured by manometry [1,2,3, 11, 12], though van Dam et al [26] reported a risk of impaired fecal continence after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is indicated for large rectoceles with a diameter >3 cm and/or symptomatic rectoceles associated with obstructed defecation, incomplete emptying, or evacuation with digital support, as described in previous studies [1,2,3,4,5,6,7,8,9,10]. To date, various techniques of surgical repair for rectoceles have been introduced with a variety of outcomes [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. However, the most promising procedure for these patients in terms of postoperative clinical outcome has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical correction of the rectocele or posterior colpocele The largest prospective multicentre trial containing 90 patients undergoing the STARR procedure for treatment of outlet obstruction caused by the combination of intussusception and rectocele has shown encouraging early results [ 35 -37 ]. All patients had signifi cant improvement in constipation symptoms without affecting continence, and postoperative defaecating proctography showed the disappearance of both the intussusception and rectocele [ 17 ]. Severe complications, however, have been reported, including bleeding, faecal urgency, incontinence, stenosis, dramatic chronic pain, constipation [ 38 ] and rectovaginal and enteral fi stulas [ 39 , 40 ].…”
Section: Type I Digitiform Rectocele or Single Hernia Through The Recmentioning
confidence: 99%
“…The technique provides the opportunity to perform endorectal rectocele removal without the risks of transabdominal procedures. This novel technique seems to be safe and effective in the treatment of outlet obstruction caused by the combination of intussusception and rectocele 5,6,7,14 . Randomized trials are required to confirm these findings.…”
Section: Discusionmentioning
confidence: 99%
“…A lumpy vaginal protrusion, vaginal bulging, and pelvic heaviness also are important symptoms that indicate the need for treatment 29 . Conservative management, including biofeedback training, can be helpful for patients with mild symptoms 20 . If conservative management fails to relieve the symptoms, surgical treatment is advocated.What constitutes the optimal procedure has been discussed for years among colorectal surgeons and urogynecologists.A large variety of surgical techniques are available for the treatment of rectocele, including transvaginal, transperineal, endorectal, transabdominal, and combined approaches 1,5,24 . In addition to the surgical technique itself, in numerous studies the question of using synthetic material for the repair of pelvic organ prolapses is addressed 3,14 .…”
mentioning
confidence: 99%